Can Science Inform Christian Ethical Reflection on Gender Identity? - Messer, Neil (Studies in Christian ethics, 2024)
This article explores whether and how research into biological influences on gender identity can and should inform Christian ethical reflection on gender diversity and gender nonconformity. First, the current state of genetic and neuroscientific research on gender identity is surveyed. While the scientific findings are as yet preliminary, tentative, and sometimes contradictory, researchers argue that they already give grounds for thinking that many biological factors have some influence on gender identity through complex interactions with many social and environmental factors. Next, the article offers some general remarks about how natural scientific findings should—and should not—inform Christian theological and ethical reflection. Finally, three specific proposals are developed for how scientific research can and should inform Christian ethical reflection on gender identity. The article offers both a contribution to this Christian ethical reflection and a case study of how the natural sciences may be used in Christian ethics.